Free fibular flap with periosteal excess for mandibular reconstruction. Issue 7 (14th August 2013) - Trignano, Emilio; Fallico, Nefer; Faenza, Mario; Rubino, Corrado; Chen, Hung‐Chi
<x xml:space="preserve">Abstract</x> Background In microvascular transfer of fibular osteocutaneous flap for mandible reconstruction after cancer ablation, good bone union is necessary to allow timely radiation therapy after surgery. As the area of bone contact between fibula and the original mandible at the edge of the mandibular defect is small, a periosteal excess at both ends of the fibula covering the bone junction can be used to increase the chance of bone union. The purpose of this study is to investigate whether a periosteal excess surrounding both ends of the fibula flap can provide better blood supply and, therefore, ensure bone union and wound healing at 6 weeks after surgery and before radiation therapy initiation. Patients and methods The transfer of fibular osteocutaneous flap with periosteal excess was only applied to reconstruct segmental mandibular defects. As a consequence, only cases in which osteotomy of fibula was not performed were included in this study. A total of 34 fibular flaps without osteotomies were performed between 2000 and 2008; 17 with and 17 without the periosteal excess. The bone union was evaluated in terms of osseous callus formation using X‐rays and CT three‐dimensional images at 6 weeks after surgery, and results were assessed by three independent radiologists. Results There was a significant difference between reconstructions with and without the periosteal excess in terms of bone union (P = 0.022). With reference to postoperative complications, the group reconstructed without periosteal excess presented a higher number of complications, mainly consisting of partial and total flap necrosis, respectively six (35.29%) and two (11.76%) cases. In the group reconstructed with periosteal excess, no loss of the skin island has occurred. A significant difference was observed in terms of partial flap necrosis (P = 0.024), while the other complications did not reveal a statistically significant difference (P > 0.05). Conclusions The use of a periosteal excess at both ends of the fibula flap provides better blood supply and is, therefore, able to ensure good bone healing and skin paddle survival regardless of the radiotherapy. © 2013 Wiley Periodicals, Inc. Microsurgery 33:527–533, 2013.